THE EFFECT OF ENTREPRENEURSHIP COURSE LEARNING OUTCOMES ON THE UNDERSTANDING OF MARKETING CONCEPTS (Al-Mubin, 2025)
Understanding the concept of marketing is an important part of entrepreneurship because it supports business strategy. The Entrepreneurship course aims to equip students with knowledge and skills, including an understanding of marketing. The learning outcomes of the Entrepreneurship course serve as an indicator of the success of learning and the students’ ability to apply the material obtained. This study aims to determine the influence of learning outcomes in the Entrepreneurship course on the understanding of marketing concepts among students of the Economic Education Study Program, Faculty of Teacher Training and Education (FKIP), Sriwijaya University, class of 2021. The study used a quantitative approach with a causal associative design. The sample consisted of 64 students, and data were collected through documentation, tests, and interviews. Data analysis techniques included descriptive statistics, prerequisite tests, and hypothesis testing. The test results showed that the value of tcount < ttable or 0.867 < 1.670, which means Ha is rejected and Ho is accepted. This indicates that there is no significant influence between the learning outcomes of the Entrepreneurship course and the understanding of marketing concepts among students of the Economic Education FKIP Sriwijaya University, class of 2021. The researcher suggests that future studies consider other variables and more diverse data collection methods to obtain more comprehensive results